Efficacy and safety of intravitreal anti-VEGF therapy in diabetic retinopathy: what we have learned and what should we learn further?. (3rd October 2022) - Uludag, Gunay; Hassan, Muhammad; Matsumiya, Wataru; Pham, Brandon Huy; Chea, Sophaktra; Trong Tuong Than, Ngoc; Doan, Hien Luong; Akhavanrezayat, Amir; Halim, Muhammad Sohail; Do, Diana V; Nguyen, Quan Dong
ABSTRACT: Introduction: Diabetic retinopathy (DR) is one of the most frequent microvascular complications of diabetes that can lead to blindness. Laser treatment has been the gold standard treatment for diabetic macular edema (DME) and proliferative diabetic retinopathy (PDR) for many years. Recently, the role of vascular endothelial growth factor (VEGF) has been established in the pathogenesis of DR, and the use of intravitreal anti-VEGF therapy has gained popularity for the management of DR. Areas covered: This review includes a brief overview of the efficacy and safety of currently available (bevacizumab, ranibizumab, and aflibercept) and potential future (brolucizumab, faricimab, and KSI-301) anti-VEGF agents in patients with DR based mainly on publicly available data from phase 1, 2 and 3 clinical trials. Expert opinion: Clinical trials investigating the efficacy of intravitreal bevacizumab, ranibizumab, and aflibercept injections demonstrated favorable functional and anatomical outcomes in patients with DME. Moreover, the use of these anti-VEGF agents showed a significant improvement in the severity of DR. Recent clinical research for future anti-VEGF molecules aims to provide higher target-protein binding affinity and prolonged therapeutic effect. Brolucizumab, faricimab, and KSI-301 are three novel anti-VEGF agents that demonstrate promising data for the management of DME and potentially DR.